The Arab modernists approach in dealing with the Holy Quran: The skeptical approach of Muhammad Arkoun as a model – a Critical study- - Al-Ghazzawi, Sana (Jordan Journal of Islamic Studies, 2023)
This study deals with modernity in terms of definition and creation, then presents the Arab modernist project outlining its objectives and its pioneers. Then it’s focuses on the work of the most important pole of modernity, namely Muhammed Arkoun. In a practical study of his method in dealing with the verses of the Holy Quran by study and research, following that purpose the researcher used Inductive and analytical approaches. The study came up with number of conclusions, including: the most important features of modernist to the Qur’anic readings is lifting the holiness from the Islamic texts, and attempting to reformulate the visions of these texts, by placing them among human texts, through several practices, these practices will be revealed in this study.